The assessment and management of chemotherapy-related toxicities in patients with breast cancer, colorectal cancer, and Hodgkin's and non-Hodgkin's lymphomas: A scoping review. (February 2017) - Fox, Patricia; Darley, Andrew; Furlong, Eileen; Miaskowski, Christine; Patiraki, Elisabeth; Armes, Jo; Ream, Emma; Papadopoulou, Constantina; McCann, Lisa; Kearney, Nora; Maguire, Roma
Abstract: Purpose: The purpose of the eSMART (Electronic Symptom Management using the Advanced Symptom Management System (ASyMS) Remote Technology) study is to evaluate the use of mobile phone technology to manage chemotherapy-related toxicities (CRTs) in people with breast cancer (BC), colorectal cancer (CRC), Hodgkin's lymphoma (HL), and non-Hodgkin lymphoma (NHL)) across multiple European sites. One key objective was to review the published and grey literature on assessment and management of CRTs among patients receiving primary chemotherapy for BC, CRC, HL, and NHL to ensure that ASyMS remained evidence-based and reflected current and local practice. Methods: Three electronic databases were searched for English papers, with abstracts available from 01/01/2004-05/04/2014. For the grey literature, relevant clinical practice guidelines (CPGs)/evidence-based resources (EBRs) from the main international cancer organisations were reviewed as were symptom management (SM) protocols from the sites. Results: After full-text screening, 27 publications were included. The majority (n = 14) addressed fatigue and focused on BC patients. Relevant CPGs/EBRs were found for fatigue (n = 4), nausea/vomiting (n = 5), mucositis (n = 4), peripheral neuropathy (n = 3), diarrhoea (n = 2), constipation (n = 2), febrile neutropenia/infection (n = 7), palmar plantar erythrodysesthesia (PPE) (n = 1), and pain (n = 4). SM protocols were provided by >40% of the clinical sites. Conclusions: A need exists for empirical research on SM for PPE, diarrhoea, and constipation. Research is needed on the efficacy of self-care strategies in patients with BC, CRC, HL, and NHL. In general, consistency exists across CPGs/EBRs and local guidelines on the assessment and management of common CRTs. Highlights: First review of the published and grey literature on assessment and management of chemotherapy-related toxicities (CRTs). Need for more research on symptom management for hand-foot syndrome, diarrhoea, constipation, peripheral neuropathy. Hand-foot syndrome, diarrhoea, and constipation are less likely to be addressed by clinical practice guidelines (CPGs). A broad consistency exists across CPGs and local guidelines on the assessment and management of commonly occurring CRTs.